A Review on Pharmacological Properties of Indian Innate Plants - Parameswari, Mohan; Jayamoorthy, Karunamoorthy; Savitha, S. (Pharmacognosy Reviews)
India's vast biodiversity includes a myriad of medicinal plants that have been utilized in traditional medicine for millennia. Plants have been integral to human health and medicine since ancient times, offering a vast array of pharmacologically active compounds with diverse therapeutic potentials. This review explores the broad spectrum of pharmacological properties exhibited by plants, encompassing antioxidant, antimicrobial, anti-inflammatory, anticancer, and other bioactive activities. These properties stem from a rich chemical diversity present in plant extracts, including alkaloids, flavonoids, terpenoids, phenolics, and essential oils. The review discusses the importance of these compounds in modern pharmacology, highlighting their roles in drug discovery, and development, and as natural alternatives to synthetic medications. Moreover, it addresses current trends, challenges, and future directions in utilizing plant-derived compounds for pharmaceutical and nutraceutical applications, emphasizing their significance in both traditional and modern medicinal practices. The integration of traditional knowledge with modern scientific approaches could lead to the development of novel treatments and improved health outcomes.
Keywords: Easily available plants; Herbs; Medicinal plants; Pharmacological properties.